2015
DOI: 10.17221/8244-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Significance of clinical variables and selected biochemical markers in predicting the outcome of bovine anaplasmosis

Abstract: ABSTRACT:The present study was aimed at evaluating the usefulness of selected inflammatory and oxidative stress markers in predicting the clinical outcome of cattle infected with Anaplasma (A). marginale. The study population consisted of 39 cattle naturally infected with A. marginale. The presumptive diagnosis of this infection was initially achieved on the basis of case history, microscopy and clinical examination findings, and confirmed using A. marginale-specific PCR assays. The diseased cattle were catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Our results revealed significantly reduced GSH and TAC in the infected cattle, which is consistent with the suggestion that [ 5 ] the decrease in GSH in cattle with A. marginale infection might be due to either elevated activity of glutathione peroxidase that utilizes GSH to reduce peroxides or to its capacity to directly detoxify ROS. In this study, reduced serum TAC in the infected cattle may result from the exhaustion of antioxidant enzymes that act as scavengers for the free-radical throughout the oxidative process that occurs during A. marginale infection of cattle [ 11 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results revealed significantly reduced GSH and TAC in the infected cattle, which is consistent with the suggestion that [ 5 ] the decrease in GSH in cattle with A. marginale infection might be due to either elevated activity of glutathione peroxidase that utilizes GSH to reduce peroxides or to its capacity to directly detoxify ROS. In this study, reduced serum TAC in the infected cattle may result from the exhaustion of antioxidant enzymes that act as scavengers for the free-radical throughout the oxidative process that occurs during A. marginale infection of cattle [ 11 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…This incidence is higher than the incidence reported previously (28%) [ 18 ] using a cELISA. A. marginale incidence was determined with DNA in sera using molecular techniques in 20.12% of animals [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the disease was detected in many governorates. In Egypt, several studies reported anaplasmosis caused by A. marginale in cattle, water buffaloes and camel [27][28][29][30][31][32]. Frequently used techniques in these reports were microscopy [30], competitive ELISA (cELISA) [33,34], immunofluorescent assay (IFA) [35,36], or molecular assays i.e., conventional PCR [27] or real-time PCR [37].…”
Section: Introductionmentioning
confidence: 99%
“…Review and Discussion In Egypt, the documented ticks transmitted diseases were 1-Anaplasmosis bovine (El-Ashker et al, 2016). 2-Babesiosis in rodents, man, dog, and equines (El Bahrawy et al, 1993;El-Bahnasawy and Morsy, 2008;Mahmoud et al, 2016), 3-Crimean-Congo hemorrhagic fever virus imported (El-Bahnasawy et al, 2012a), 4-Lyme disease tick and man (Adham et al, 2010;Elhelw et al, 2014;Saleh et al, 2016), 5-Tickborne relapsing fever (El-Bahnasawy et al, 2012b), 6-Theileriosis in ruminants, cattle, sheep and equines (Mazyad and Khalaf, 2002;Els-ify et al, 2015;Mahmoud et al, 2016), and 7- Ghoneim et al (2017) in Egypt studied role of camels and attached ticks in Francisella species epidemiology.…”
Section: Introductionmentioning
confidence: 99%